2001
DOI: 10.1046/j.1365-2036.2001.00922.x
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug reactions in patients with gastroenterological diseases: does age increase the risk?

Abstract: Background: It has been claimed that the risk of adverse drug reactions increases with age. However, only limited data exist for disease‐group specific risks and none for patients with liver and gastrointestinal diseases. Aims: To determine the incidence and characteristics of adverse drug reactions and the physicians’ awareness of adverse drug reactions. Methods: During a 7‐month period, a prospective survey of 532 male patients (158 aged 65 years or older; 30%) was conducted on a hepatogastroenterological wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 37 publications
1
25
1
Order By: Relevance
“…[31] In the same way, age is usually considered as an independent risk factor for ADRs or for their serious nature, though this has been disputed. [12,13,31,32] In the current study, there is a clear and significant risk gradient in point estimates (from 1 for those below 75 years of age to 1.9 in those 85 years of age and above), although the risk did not appear significantly increased for patients aged 75-79 years or those aged 80-84 years compared with patients aged below 75 years. The association of the use of analgesic drugs with a significantly lower risk of reporting serious (rather than non-serious) ADRs has no clear pharmacological explanation.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…[31] In the same way, age is usually considered as an independent risk factor for ADRs or for their serious nature, though this has been disputed. [12,13,31,32] In the current study, there is a clear and significant risk gradient in point estimates (from 1 for those below 75 years of age to 1.9 in those 85 years of age and above), although the risk did not appear significantly increased for patients aged 75-79 years or those aged 80-84 years compared with patients aged below 75 years. The association of the use of analgesic drugs with a significantly lower risk of reporting serious (rather than non-serious) ADRs has no clear pharmacological explanation.…”
Section: Discussioncontrasting
confidence: 47%
“…These characteristics have been shown to constitute individual risk factors for adverse events and for serious adverse events with drugs in general. [12,13] According to a previous study, more than 50% of subjects aged 65 years or over use cardiovascular system drugs, including agents prescribed for arrhythmias and drugs that can induce arrhythmias. [14] The prevalence of respiratory comorbidities is not that high but many drugs used by the elderly can affect respiratory function; an example is benzodiazepines, which are consumed by many elderly subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Based on a study on the incidence of lethal adverse drug reactions in hospitalised patients in the United States 106.000 lethal ADR per year are expected [27]. Data on the incidence of ADR are mainly available for hospitalised patients [1][2][3][4][5][6][8][9][10][11][12][15][16][17][18][19][23][24][25][26][27][28]33,36,37,38,39]. Due to the study design and the evaluation of the outcome of the incidence varies considerably between different studies.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, enoxaparin has been associated with severe adverse drug events (ADE), such as bleeding, skin reaction, liver failure, and anemia [6–8]. ncreasing age is a common risk factor for ADE with many types of medication [911], and enoxaparin is no exception. Macie et al suggested that increasing age was a risk factor for bleeding during treatment with enoxaparin [12].…”
Section: Introductionmentioning
confidence: 99%